Effects of mechanical grinding on the physicochemical properties of silica aerogels - Li, Rutian; Zeng, Shuisheng; Shen, Kai; Wang, Guichao; Zhang, Jun (Frontiers in Materials, 2023)
Mechanical grinding is a facile method to get silica aerogels (SAs) with various particle sizes. However, the relationship between the grinding parameters and physicochemical properties is still unclear. In this study, we concentrated on the effects of grinding time and grinding speed on the physical and chemical properties of silica aerogels. The results reveal that the physicochemical properties of silica aerogels are more sensitive to the grinding speed rather than the grinding time. When the grinding speed is over 200 rpm, large particles of silica aerogels are crushed into smaller particles with obviously decreasing particle sizes and the silica skeletons of silica aerogels have collapsed. The reduction of particle sizes and the collapse of skeleton lead to an increase in both the tap density and thermal conductivity. Therein, the thermal conductivity is positively proportional to the density. Furthermore, the grinded silica aerogels powders still possess the contact angles over 135°, indicating the good hydrophobicity. All these demonstrate that the mechanical grinding has evident effects on the microstructure, density, thermal conductivity and particle sizes, which further impact the performance of silica aerogels during the practical applications. Given the expanding applications of SAs across various industries, the study serves as a valuable reference for optimizing the mechanical post-treatment of SAs, facilitating the achievement of desired particle sizes. Ultimately, this research holds great potential in diversifying the application fields of SAs in their powdered form.